PENGARUH KERJASAMA TIM DAN KREATIVITAS TERHADAP KINERJA KARYAWAN UD. AGRO INTI SEJAHTERA JEMBER - andi Febriyan Eka Muhti; Hadi Sunaryo; Muhammad Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2017)
ABSTRACT The purpose of this study to determine the effect of Teamwork and Creativity simultaneously and partially on UD Employee Performance. Agro Inti Sejahtera Jember. The sampling technique using random sampling. Data analysis tool used in this research is multiple linear regression analysis.            Based on the results of this study note that the count value of 73.899 with a value of 0.000 <0,05 so that it can be concluded that Teamwork and Creativity affect simultaneously to Employee Performance. And partially effect on Employee Performance. And there is one variable that is Team Cooperation variable which has no partial effect.Keywords: Teamwork, Creativity and Employee Performance